Dampak Era Society 5.0 Terhadap Kompetensi Perekam Medis dan Informasi Kesehatan (PMIK) - Ade Fatima (Jurnal Rekam Medis dan Informasi Kesehatan, 2023)
The era of society 5.0 creates new challenges in various sectors of life, one of which is the health sector. Health development is directed at realizing optimal health degrees. To achieve this goal, it is necessary to manage various resources so that efficient, quality, and affordable health services can be available. At this point, a quality medical recorder is needed. In the era of society 5.0 every individual must have knowledge and skills. This relates to the PMIK competency field at number 2, namely Self-Introspection and Self-Development. The influence of the era of society 5.0 on PMIK's competence has led to changes and improvements in knowledge that require PMIK to be able to develop, apply and use technology, one example of its use is Electronic Medical Records (RME) and Hospital Management Information Systems (SIMRS). The purpose of this study was to determine the influence and relationship of the era of society 5.0 on PMIK competence. This study uses a qualitative data interpretation method. This type of method is used to analyze data in qualitative research or also called categorical data. The subject of this research is PMIK and the object is PMIK competence in the era of society 5.0. The potential result of applying the influence of the era of society 5.0 to PMIK competence is a change in competence in line with the demands of the times. This change led to renewal of competencies taught to PMIK candidates.